Formasi Spiritual, Kepemimpinan Kristen, dan Pemuridan Transformatif: Sebuah Kerangka Integratif - Sabda Wahyudi; Ayub Sugiharto (Angelion, 2026)
This article aims to analyze the conceptual relationship between spiritual formation, character formation, Christian leadership, and transformative discipleship and to formulate an integrative framework for church discipleship praxis. The study employs a qualitative approach through a theological literature review and conceptual analysis of scholarship on spiritual formation, Christian leadership, and discipleship. The findings indicate that spiritual formation is a holistic process of transformation through the work of the Holy Spirit toward Christlikeness, encompassing spiritual, emotional, relational, intellectual, vocational, physical, and stewardship dimensions. Such formation provides the foundation for character development, which is subsequently embodied in Christian leadership through modeling, equipping, mentoring, and empowering others. Leadership rooted in spiritual formation creates a relational context for discipleship oriented toward the transformation and reproduction of disciples. The novelty of this study lies in formulating an integrative framework that understands spiritual formation, character, leadership, and discipleship as interrelated and circular processes. This framework calls the church to develop discipleship as a culture of life formation centered on Christlikeness.   Artikel ini bertujuan menganalisis hubungan konseptual antara formasi spiritual, pembentukan karakter, kepemimpinan Kristen, dan pemuridan transformatif serta merumuskan kerangka integratif bagi praksis pemuridan gereja. Penelitian menggunakan pendekatan kualitatif melalui studi literatur teologis dan analisis konseptual terhadap literatur mengenai spiritual formation, kepemimpinan Kristen, dan pemuridan. Hasil kajian menunjukkan bahwa formasi spiritual merupakan proses transformasi holistik melalui karya Roh Kudus menuju keserupaan dengan Kristus yang mencakup dimensi spiritual, emosional, relasional, intelektual, vokasional, fisik, dan penatalayanan. Formasi tersebut menjadi fondasi pembentukan karakter yang kemudian diwujudkan dalam kepemimpinan Kristen melalui keteladanan, memperlengkapi, mendampingi, dan memberdayakan. Kepemimpinan yang berakar pada formasi spiritual menciptakan konteks bagi pemuridan relasional yang berorientasi pada transformasi dan reproduksi murid. Kebaruan penelitian terletak pada perumusan kerangka integratif yang memandang formasi spiritual, karakter, kepemimpinan, dan pemuridan sebagai proses yang saling berkaitan dan bersifat sirkular.